Knowledge, awareness, and breast self-examination practice among nurses in Sultan Ahmad Shah Medical Centre: a follow-up 6 months study - Sowtali, Siti Noorkhairina; Mohamed Faizal, Fadhlin Farhanah (Kulliyyah of Allied Health Sciences, International Islamic University Malaysia, 2023)
Background: Nurses play an important role as public health educators, particularly in breast cancer screening. Therefore, follow-up studies on breast cancer and breast self-examination (BSE) are important to ensure that nurses’ knowledge is updated. The objectives are to determine the knowledge, awareness, and practice (KAP) of breast cancer and BSE among staff nurses in SASMEC@IIUM in Kuantan, Pahang, and its association with socio-demographic factors. Methodology: A quasi-experimental study was conducted among 50 nurses. A validated questionnaire was utilised to assess the KAP of BSE domains. Data was analysed for descriptive statistics and Wilcoxon signed-rank test to compare the changes. Results: A total of 50 nurses were involved in the pretest. However, only 30 nurses were retained at the 6-month posttest. Most were females (86.7%), Malay (96.7%), married (66.7%), with a family history of cancer (26.7%), and have a family history of breast cancer (13.3%). Positive improvements were observed in their median scores for knowledge and practice related to BSE domains post-6-month. A significant association was noted between knowledge of the risk factors among the nurses posttest (p = 0.015). Conclusion: The webinar on breast cancer improved the nurses’ knowledge of breast cancer risk factors. Continuous effort is vital to sustain the positive changes in BSE practice and improve the nurses’ awareness of delivering health education on breast cancer. An intervention that integrates digital technology is perhaps needed in the future to achieve a better outcome.